Digital Transformation of Subjective Civil Rights: Problems and Prospects - N. V. Razuvaev (Теоретическая и прикладная юриспруденция)
The article examines the phenomenon of digital transformation of subjective civil rights, which is the most important characteristic of civil circulation in the information society. According to the author, digital transformation is a systemic change in the main features and content of subjective law under the influence of digital technologies, with the help of which new types of property are constructed, namely cryptocurrencies, digital rights, tokens, databases, and other virtual objects. The characteristic properties of such objects, first of all, the absence of a material substrate, that is, physical, material expression, make it difficult to characterize them as things, in the traditional meaning of this concept.However, the needs for the development of civil turnover in the context of the digitalization of the economy makes it necessary and inevitable for the participation of various types of digital property as objects of both property and contractual rights. The civil circulation of digital objects becomes possible as a result of endowing the latter with the properties of things or actions, which implies the formation of appropriate legal regimes. Since the legal regime, as shown in the work, includes three main elements, namely, objects of rights, subjective civil rights and regulatory means, digital transformation affects all these elements, contributing to their modification.At the same time, the main attention in the work is paid precisely to subjective civil rights, which, in a situation of underdeveloped regulatory regulation, are the main regulator of digital property turnover. Considering the prospects for the digital transformation of subjective civil rights in the context of the digitalization of civil law and order, the author comes to the conclusion that the processes considered in the work will affect not only the sphere of property rights, but also the personal non-property rights of subjects. The analysis performed allows us to formulate some proposals for improving the current civil legislation, contributing to its further reform.